The Liberation Revolution Image in Popular Poetry: The “Poems from the Revolution of the Free” Collection by Ahmed Qaja - بوجرة سميرة (Milev Journal of Research and Studies, 2023)
What hallmarks the current study is that it attempts to cast light upon the image of the liberation revolution in popular poetry through the lenses of the model whose label is "Poems and Poems from the Revolution of the Free" by the popular poet Ahmed Qajah, who is one of the local poets of the Mila province. The study has striven to answer each of the following primary research questions: 1) how is the liberation revolution image depicted in the collection of “Poems from the Revolution of the Free”? And 2) to what extent did the poet succeed in portraying the history of the liberation revolution through popular poetry? The primary aim behind conducting the present study was to capture the image of the Algerian liberation revolution in this creative poetic style, and to bring to the light of day the intellectual and artistic values of popular poetry and its manifold role in preserving history and indoctrinating the rising generations with national values. To track the major as well as the minor themes of the subject, the study adhered to the thematic approach, wholly depending on the mechanisms of analysis, description and conclusion. It is abundantly clear that in his divan, the popular poet Ahmed Qaja succeeded in immortalizing the history of the liberation revolution. That has been accomplished through a fascinating depiction of its most crucial, glorious events and its free heroes. He mixes history with beautiful poetic creativity; he takes from these events the material for poetic images, which are full of noble patriotic feelings, which attracts the audience to this glorious history.